1993
DOI: 10.1246/bcsj.66.2900
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of the Reaction of Nitrous Acid with Iodide Ion in the Presence of Molecular Oxygen in an Acid Solution

Abstract: The kinetics of the reaction between nitrous acid and iodide ion were studied in the presence of molecular oxygen (O2) in an acid solution (pH 1.9—3.1); much larger amounts of the triiodide ion than expected from the amounts of nitrous acid were formed under conditions of the iodide ion in excess over nitrous acid. The initial rates for the formation of I2 and I3− increased proportionally with increasing both the O2 and nitrous acid contents, and increased greatly with decreasing the pH in the solution. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…Light over the reaction vessel and ambient oxygen had no apparent effects on the Br À oxidation; whereas, it has been reported that air, or oxygen gas, affected the oxidation of I À into I 3 À . 20,21 Dilute nitric acid with concentration in the 0.25-2.5 mol dm À3 (in 1.0 vol % H 2 O) range produced almost the half-amount Br 2 molecules to each HNO 3 molecules. Considering the amount of the product, the formation of Br 2 (or Br 3 À ) seems to follow the reaction in Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light over the reaction vessel and ambient oxygen had no apparent effects on the Br À oxidation; whereas, it has been reported that air, or oxygen gas, affected the oxidation of I À into I 3 À . 20,21 Dilute nitric acid with concentration in the 0.25-2.5 mol dm À3 (in 1.0 vol % H 2 O) range produced almost the half-amount Br 2 molecules to each HNO 3 molecules. Considering the amount of the product, the formation of Br 2 (or Br 3 À ) seems to follow the reaction in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…8 we observed that a rather strong yellow-color developed only when (dilute) nitric acid was present in Br À ion rich conditions; the possibility of formation of yellow-colored cobalt(II) and cobalt(III) complexes was denied by our careful examination of many cobalt complexes. Kimura et al 20,21 have reported the reactions of nitrous and phosphinic acids with the iodide ion in the presence of molecular oxygen in acidic solutions.…”
mentioning
confidence: 99%
“…The reactive medium must contain some nitrogen monoxide resulting from reaction (R-4) or, more hypothetically, from the dismutation of nitrous acid in acidic medium (this reaction being much slower than reaction (R-3) [14]). The catalysis of reaction (R-9) by nitrogen monoxide has been reported by Eguchi et al [15,16], whose results were confirmed by Kimura et al [17]. It occurs according to the following mechanism: the sum of (R-11), (R-12) and (R-4) resulting in (R-9).…”
Section: Role Of Dissolved Oxygenmentioning
confidence: 57%
“…The mechanism of iodine formation in the blank test is not completely clear, since even solutions deaerated by bubbling argon gas, revealed some presence of iodine under longer irradiation of the sample at excitation wavelength. Probably a trace amount of oxygen is sufficient for an initial formation of iodine whose concentration further increases as a result of chain photochemical reactions involving free iodine radicals [14]. On the other hand, no clear effect of the deaeration on the reaction rate of iodide with NO2 has been observed, although a catalytic effect of oxygen on reaction (1) was observed in classical systems containing KI at high concentration (0.1 M) [ 14,15].…”
Section: Landol> Type Reaction In the System: Noi; -I--$202 -mentioning
confidence: 99%
“…Probably a trace amount of oxygen is sufficient for an initial formation of iodine whose concentration further increases as a result of chain photochemical reactions involving free iodine radicals [14]. On the other hand, no clear effect of the deaeration on the reaction rate of iodide with NO2 has been observed, although a catalytic effect of oxygen on reaction (1) was observed in classical systems containing KI at high concentration (0.1 M) [ 14,15]. These differences probably result from the application of a micellar system, in which the concentration effect favours the reacting anions over neutral oxygen molecules.…”
Section: Landol> Type Reaction In the System: Noi; -I--$202 -mentioning
confidence: 99%